Virtual Theater, or about Searching for A New Form of Theater Online - Natalia V. Nikulicheva; Olga S. Glukhovskaya; Vladimir A. Gagarin (Открытое образование (Москва))
They have been talking about the search for a new form of theater for a long time, but in addition to the online broadcast of the stage play or the actor’s performance via videoconference with the reading of the literary text, no ideas are offered. Moreover, here pedagogy can contribute to the search for a new form. The theater has always been used in pedagogy as a method, and the regularities of the organization of distance learning will help to transfer it to the format of virtuality. The question arises - how exactly to do this so that not only theater is available for full-time students at school (college, university), but also for distance learning? In general, for those categories of citizens who cannot attend the theater, but would like to attend performances or engage in theatrical art remotely? The purpose of this study was the desire to put into practice the theoretical assumption of transferring theatrical action to virtuality. If you just turn on the online broadcast of the performance or show it in the recording, then the theater automatically turns into a movie, and not into a very high-quality one, since the camera does not keep up with all the movements of the actors, and the microphone captures unnecessary sounds from the audience. There is a way to organize a new theater format - through avatar management and voice acting of heroes in 3D space. If we understand the possibilities of the virtual environment in terms of the transmission of emotions, experiences, plots, then it is logical to assume that virtual theater is a role-playing game format, one of the methods of pedagogy. Once in a new environment (in this case, in a virtual environment), a person changes his behavior, begins to feel and react differently. Today there are already several studies on teaching children and adults in virtual reality. This article describes the experience of organizing a virtual theater with all its inherent attributes: selection of a script, preparation of actors, creation of scenery, costumes, rehearsals, preparation of posters, invitation of spectators and performance online. The virtual performance was held in the 3D world “Virtual Academy”. Students of 5-7 grades acted as actors, teachers of a school, college and university acted as organizers. The work also included parents of artists who quickly solve technical problems with home computers, which made it possible to prepare the performance in a short time (about 1,5 months). All participants in the performance were interested in the process, worked very responsibly, were satisfied with the result and expressed the desire to continue such productions. The description of the methodology for organizing a virtual theater will allow in the future using this method to work with both schoolchildren in distance learning conditions and with students of theater universities to study the specifics of theatrical art in virtuality.